Effect of Dietary Supplementation of Azolla Meal on Feed Intake and Digestibility in Sangamneri Kids - P. P. Bhadake; M. G. Mote; U. S. Gaikwad; M. U. Tanpure (Indian Journal of Animal Nutrition, 2024)
Twenty-four Sangamneri kids aged between 3 to 6 months and weighing between 8 to 12 kg were selected for the experiment and distributed into four treatments viz., T0 (control), T1 (10 % concentrate replaced by Azolla meal), T2 (15% concentrate replaced by Azolla meal) and T3 (20 % concentrate replaced by Azolla meal). The feeding trial was conducted for the period of 3 months. Roughages to concentrate ratio was kept as 67:33. Feed samples and faeces of different treatments were collected and chemically analyzed. The DM, CP, CF, EE, NFE, total ash, lignin and silica content in Azolla meal were 92.12, 22.41, 16.30, 2.87, 53.15, 7.90, 9.35 and 3.12 percent respectively and the concentrate mixture had 90.23, 19.13, 8.2, 4.95, 62.82, 4.6, 1.72 and 1.31 percent DM, CP, CF, EE, NFE, total ash, lignin and silica respectively. Average daily dry matter intake was 0.405, 0.520, 0.590 and 0.509 (kg/day) in T0, T1, T2 and T3 respectively. Average DM intake per 100 kg body weight during period of experiment were 2.86, 3.57, 3.81 and 3.50 per cent. Feed consumption difference due to different treatments were found statistically significant (P<0.5). Feed conversion efficiency w-as highest in treatment T0 (16.65 %) followed by T2 (16.18 %), T3 (15.43 %) and T1 (14.56 %). The inclusion of 15 % Azolla in feed was found to be effective looking to the total weight gain in different treatments. Digestibility of DM differed significantly (P<0.5) between different treatments. Higher digestibility of DM was observed in T0 followed by T1, T2 and T3 respectively. This might be due the increasing level of lignin which reduces the digestibility of DM. The digestibility of the CP, EE and lignin was highest in the T0 group followed by T1, T2 and T3 and there was significant difference (P<0.5) among different treatments. This clearly indicated that the increase in Azolla level decreases the EE digestibility. Digestibility of CF and NFE showed significant difference at 5 per cent among different treatments. Highest digestibility of CF and NFE was in T0 followed by T2, T1 and T3.